SIBISA-BASED ONLINE COMPLAINT SERVICE FOR ELECTRONIC RESIDENT ID CARD (E-KTP) PROCESSING AT THE POPULATION AND CIVIL REGISTRATION SERVICE OF MEDAN CITY - Yulia Christy Naibaho; Tunggul Sihombing (Yayasan Wayan Marwan Pulungan, 2025)
Many people still believe that the use of SIBISA in population document services is not functioning optimally. The community remains reluctant to use the complaint facility due to limited understanding of technology and the lack of comprehensive socialization. As a result, many citizens are unaware that complaints can be submitted online. In addition, weak supervision of incoming complaints contributes to low public trust in the responsiveness of the system. Some people also hesitate to report service-related issues because they fear potential consequences and assume that complaint resolution will take a long time. This study employed a descriptive qualitative approach. Data were collected through interviews, observations, and documentation. The data were analyzed qualitatively using Papadomichelaki’s (2012) e-GovQual framework, which includes four indicators of electronic government service quality: efficiency, reliability, trust, and citizen support. The findings show that the Online-Based Electronic Identity Card (KTP-E) Complaint Service at the Medan City Population and Civil Registration Office has not been fully realized. Interviews indicate that service employees generally prioritize community needs; however, the high volume of services compared to the available workforce makes consistent prioritization difficult. Moreover, the lack of intensive socialization regarding the online complaint service has caused continuous reliance on manual services. To address this issue, broader outreach through social media, websites, and public announcements at the Medan City Population and Civil Registration Office is needed. Improved socialization will help citizens understand how to use the online complaint system properly and gradually reduce dependence on conventional service methods.